HUBUNGAN PERILAKU HIDUP BERSIH DAN SEHAT TERHADAP ANGKA KEJADIAN PNEUMONIA PADA BALITA DI RUMAH SAKIT SITI KHODIJAH SEPANJANG SIDOARJO TAHUN 2019 - Gina Noor Djajilah; Ummu Khonsa; Afrita Amalia Laitupa; Sholihul Absor (Universitas Muhammadiyah Surabaya, 2023)
Pneumonia is still the leading cause of death in children under five with four million deaths in developing countries. In Indonesia, the incidence in infants and toddlers ranges from 10 - 20% per year (Maryunani, 2010). In Indonesia alone, the incidence of pneumonia in children under five in 2016 reached 568,146 cases (4.0%) out of a total number of 13,960,310 children under five in Indonesia, which ranked first on the list of deadly diseases in toddlers (Kemenkes RI, 2017; Ellita, 2013). To analyze the relationship between Clean and Healthy Living Behavior (CHLB) on the incidence of pneumonia in children under five at Siti Khodijah Hospital Sepanjang Sidoarjo. This study used a retrospective design with a total sampling technique of pneumonia in children under five years old at Siti Khodijah Muhammadiyah Hospital Sepanjang Branch in March 2020 – May 2021. Data sampling using patient medical records and questionnaires. The analysis using univariate test, bivariate with chi square and multivariate with logistic regression. From the 48 respondents after being tested on univariate analysis, it was found that the univariate indicators of doing physical activity every day category achieved the highest as many as 43 people (89.6%) and the least in the category of eradicating larvae at home as many as 21 people (43%). Bivariate using the chi square test stated that there were significant indicators of a relationship, including exclusive breastfeeding (p = 0.000), not smoking in the house (p = 0.000), using clean water (p = 0.004), eradicating larvae at home (p = 0.000) and consumption of fruits and vegetables every day (p=0.000), washing hands with clean water and soap (p=0.001) and there was no significant relationship between pneumonia in children under five at Siti Khodijah Hospital Sepanjang Sidoarjo because the symp value was not valid. Sig (2-sided) and shows p>0.05, namely CHLB delivery assisted by health workers (p=0.746), weighing infants and toddlers (p=0.266), using healthy latrines (p=0.241) and doing physical activity every day. days (p=0.111). The CHLB indicator has a p value (sig) of 0.000 <0.05, which means that the CHL variable is related to the incidence of pneumonia in children under five at Siti Khodijah Hospital Sepanjang Sidoarjo. The highest OR value is on the indicator of not smoking in the house, which means that smoking in the house is at risk of 5,849 times higher. In the multivariate test using logistic regression, there was no effect on each indicator the value of p value (sig) > 0.05 because the logistic regression test did not meet the requirements sample. The indicator of doing physical activity every day category achieved the highest as many as 43 people (89.6%). There are significant indicators through the chi square test, namely providing exclusive breastfeeding (p = 0.000), not smoking in the house (p = 0.000), using clean water (p = 0.004), eradicating larvae at home (p = 0.000) and consuming fruit and vegetables every day (p=0.000), washing hands with clean water and soap (p=0.001). Indicators of Clean and Healthy Living Behavior have a p value (sig) of 0.000 < 0.05, which means that the variable of Clean and Healthy Living Behavior is related to the incidence of pneumonia in children under five at Siti Khodijah Hospital Sepanjang Sidoarjo. The logistic regression test did not meet the sample requirements.Keywords: Pneumonia, Clean and Healthy Living Behavior, Pneumonia in Toddlers